2010
DOI: 10.1073/pnas.0914318107
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of growth factor binding and specificity by VEGF receptor 2

Abstract: Vascular endothelial growth factors (VEGFs) regulate blood and lymph vessel formation through activation of three receptor tyrosine kinases, VEGFR-1, -2, and -3. The extracellular domain of VEGF receptors consists of seven immunoglobulin homology domains, which, upon ligand binding, promote receptor dimerization. Dimerization initiates transmembrane signaling, which activates the intracellular tyrosine kinase domain of the receptor. VEGF-C stimulates lymphangiogenesis and contributes to pathological angiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
209
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(216 citation statements)
references
References 47 publications
(52 reference statements)
6
209
0
1
Order By: Relevance
“…This seems to be a common mechanism in type III RTK activation (37)(38)(39)(40). Previous studies found similarities in the ligand-binding modes for type III and IV RTKs and almost identical homotypic interactions in VEGFR-2 D7 and KIT D4 (18,24,32). The VEGFR-3 structures shown here indicate additional similarities to type III RTKs; however, our results also demonstrate some unique properties of these receptors that affect the mechanism of activation.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This seems to be a common mechanism in type III RTK activation (37)(38)(39)(40). Previous studies found similarities in the ligand-binding modes for type III and IV RTKs and almost identical homotypic interactions in VEGFR-2 D7 and KIT D4 (18,24,32). The VEGFR-3 structures shown here indicate additional similarities to type III RTKs; however, our results also demonstrate some unique properties of these receptors that affect the mechanism of activation.…”
Section: Discussionmentioning
confidence: 61%
“…So far, KIT seems to be the only type III/V RTK that directly uses D1 for ligand binding (22). D1 may have a positive impact on D2 structural stability, as demonstrated by the poor resolution of the first strand of D2 (βA) in the multiple VEGFR-2 D2-3 structures, which lack D1 (18,30). On the other hand, VEGFR-3 D1 has large disordered regions in the ligand complex, suggesting that it may interact with other binding partners in vivo, such as neuropilin-2 or the large N-and C-terminal propeptides of VEGF-C and VEGF-D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Mutations in cysteine 117 result in increased dimer stability and activity, 19,22 without changes in receptor binding affinity. 21,22 In the naturally occurring mutation that we identified (V118M), the change from a more compact and rigid valine to a longer and more flexible methionine might result in rearrangement of the VEGF-D core and generate an increased area of dimer interface. The exact extent of those rearrangements could be further evaluated in structural studies of the system.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-D has an additional cysteine 117, 19,21 which interferes with the disulfide bridge, explaining why VEGF-D exists predominantly as a noncovalently linked homodimer. 6 Mutations in cysteine 117 result in increased dimer stability and activity, 19,22 without changes in receptor binding affinity.…”
Section: Discussionmentioning
confidence: 99%